'Left behind' people, or places? The role of local economies in perceived community representation. (August 2019) - McKay, Lawrence
Abstract: Modern economics attributes importance to spatial inequality: yet in studying discontent with politics, existing research has mostly neglected local contexts and attitudes people hold about them. I use British Election Study data to investigate the factors leading people to believe their community is ignored by the political process. Firstly, real economic contexts play a role, since residents of low-income communities tend to take more negative views about how well their community is represented. Secondly, negative perceptions of the local economy are associated with more negative views of community representation, whereas equivalent 'egotropic' measures of people's personal economic situation have no such effect. Thirdly, I observe a 'grievance' effect wherein people are particularly negative about community representation when they believe that the national economy is more successful than that of one's local community. Highlights: Perceived 'community representation' (CR) different to more generalised system attitudes. Low-income places have more negative views of how their communities are represented. Views of local economy linked to views of community representation. Seeing local economy as worse than national linked to negative views of CR.